Construção de consenso Delphi das competências em otorrinolaringologia necessárias ao médico para atuação na atenção primária - Rodrigues, Carolina de Castro Santos (2020)
Introduction: Otorhinolaryngological disorders are amongst the most prominent frequent diseases in primary care. The overload in secondary care could be a consequence of the low resolution of these problems in primary care. A deficiency in medical training during graduation could be a possible explanation for this fact. The average estimated hour spent in otolaryngology practice is 0.6% of the total average practice hours. Data acquired after analyzing 141 matrices of medical courses in Brazil, corresponding to approximately 70.5% of the medical schools in operation in 2013. Objectives: The present study aims to reach a consensus about the competencies in otorhinolaryngology specialty for generalists whose formation emphasis primary attention Methods: A questionnaire was created addressing the otorhinolaryngological skills relevant to the clinical practice of primary care physicians based on the competency-based curriculum for family and community medicine (2015). The electronic format of Delphi methodology was used, later on the questionnaire was sent to 20 specialists trained in three distinct specialties, the heterogeneity among the specialists contributed to ensure the results reliability. The results obtained after each round were analyzed by one researcher and validated by another researcher, observing the dissonant trends and opinions, as well as their justifications. The proposition exclusion criterion was used when the convergence of the answers in numbers 1 and 2 on the Likert-type rating scale was equal or greater than 75% and the proposition inclusion when the convergence in answers in numbers 5 and 6 of the same scale equal or greater than 75%. By the end of the results systematization and compilation, a new questionnaire was elaborated and resent, starting a new round until a consensus in all competencies were established. Results: Five rounds were performed until a consensus was establish in all 17 otorhinolaryngological competencies evaluated by the propositions. Conclusions: The data obtained by this work can serve as basis and guidelines for developing an otorhinolaryngological curriculum in undergraduate medical courses since there was no consensus in the literature about establishing the minimum otorhinolaryngological competences in the undergraduate curriculum formation. In Brazil, there is no curriculum model recommended by national guidelines